Research on the influence of design characteristics on the performance of large class city buses - Shevchenko, Inna; Dmytriiev, Illia; Dmytriieva, Oksana; Шевченко, Інна Юріївна; Дмитрієв, Ілля Андрійович; Дмитрієва, Оксана Іллівна (Харківський національний автомобільно-дорожній університет, 2022)
Problem. The relevance of the problem under consideration is due, firstly, to the traditionally highest share of road transport in the structure of passenger transportation, and, secondly, the predominance (more than 75 %) of transportation by large class city buses in the structure of road passenger transportation. Under such conditions, improving the performance of large class city buses is of particular relevance. Goal. The goal of the article is to study the influence of design characteristics on the performance of large class city buses. Methodology. The research on the influence of design characteristics on the performance of city buses employs the following methods: the method of analysis and synthesis, systems approach, the observation method, comparative analysis, factor analysis, simulation modeling, and the experimental method. Results. The results of the conducted analysis have allowed the authors to develop and test a methodology for assessing the effect of carrying capacity on the performance of large-class city buses; to develop and test a methodology for assessing the impact of speed characteristics on the performance of large-class city buses; to conduct a factor analysis of the influence of design characteristics on the performance of large-class city buses. Originality. The research has made it possible to get an insight of the influence of design characteristics (in particular, carrying capacity and speed) on the performance of large class city buses. Practical value. The results obtained can be recommended to enterprises engaged in passenger urban transportation for determining the carrying capacity of buses, which is the major characteristic set when designing a new model of a city bus.
Дослідження впливу конструкційних характеристик на продуктивність міських автобусів великого класу
Keywords: performance; urban transport; bus carrying capacity; speed; design characteristics; продуктивність; міський транспорт; місткість автобусів; швидкість руху; конструкційні характеристики; 338.3+629.3; 10.30977/AT.2019-8342.2022.50.0.06